Complete linear mitochondrial genomes for Cephea cephea and Mastigias albipunctata (Scyphozoa: Rhizostomeae), with an analysis of phylogenetic relationships - Kei Chloe Tan; Cheryl Lewis Ames; Allen G. Collins (Mitochondrial DNA. Part B. Resources)
Jellyfishes of the order Rhizostomeae include ecologically and economically important species predisposed to forming massive aggregations. This study reports the first complete mitochondrial genome of two rhizostomes: Cephea cephea (Forskål, 1775) and Mastigias albipunctata Stiasny, 1920. The linear mitochondrial genomes are 16,667bp and 16,707bp in length and 65.5% and 68.4% AT respectively; each comprises 15 protein-coding genes (PCGs; dpo, orf314, cox1-3, nd1-6, nd4L, atp6, atp8 and cytB), two ribosomal RNAs (16S and 12S rRNA), and two tRNAs (trnM and trnW). The phylogenetic analysis reveals strong support for monophyly of the suborder Kolpophorae and Cephea cephea of the infraorder Actinomyaria as sister to Krykomyaria which includes Mastigias.